Review of recent molecular pathology of bladder urothelial carcinoma - Peng Su; Ying Yang; Hong Zheng (Discover Oncology)
Abstract Bladder urothelial carcinoma (BUC) is a common malignant tumour with a high recurrence rate and mortality. Research on the molecular pathological basis of BUC is extensive. However, the specific pathogenesis and effective treatment of BUC remain to be further studied. Studies on mutation spectrum, DNA methylation, non-coding RNA, proliferation and apoptosis signalling pathways, cell cycle control, transcription factors, DNA damage repair, immune checkpoint and tumour microenvironment have provided therapeutic strategies for the diagnosis, treatment and prognosis evaluation of BUC. This study provided new insights into the molecular pathology of BUC, helped to improve the diagnosis, treatment and prognostic evaluation of patients and drove the use of precision medicine in the treatment of BUC.